Development of add-ins macros for animation of digital logic circuits in microsoft powerpoint - Kyaw, Thura (2014)
For any work or learning environment, Microsoft PowerPoint is the most use software when it comes to presentation. It is easy to modify the presentation for a specific target audience. It has not only simple design but also powerful multimedia support. It simply makes presentation more exciting than handwritten paper or any word-processing software. Normally PowerPoint presentation slides are used for similar format or themes. Some jobs are doing repeatedly over and over again. Macro plays important role for this.